2013
DOI: 10.1002/ejoc.201300641
|View full text |Cite
|
Sign up to set email alerts
|

Oxazolone‐Based Photoswitches: Synthesis and Properties

Abstract: The synthesis, photophysics and photochemistry of a family of molecular switches inspired by the green fluorescent protein (GFP) chromophore is presented. These compounds can be synthesized in one step and good yields, their photophysical properties may be tuned by the substituents, solvent and wavelength of irradiation, and they show very efficient and fast photoisomerization. Furthermore, their high thermal stability and limited photodecomposition could allow these switches to be used in a range of applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Local absorption maxima in the 330–350 nm range are common for oxazolone compounds, but extension of the heterocycle’s conjugation system results in a bathochromic shift (44), as observed for Oxa A in Mbn, which is adjacent to an additional ketone group in lieu of the N-terminal amine. Copper binding by the oxazolones both quenches fluorescence emission intensity and alters their absorption maxima (43).…”
Section: Methanobactinsmentioning
confidence: 94%
“…Local absorption maxima in the 330–350 nm range are common for oxazolone compounds, but extension of the heterocycle’s conjugation system results in a bathochromic shift (44), as observed for Oxa A in Mbn, which is adjacent to an additional ketone group in lieu of the N-terminal amine. Copper binding by the oxazolones both quenches fluorescence emission intensity and alters their absorption maxima (43).…”
Section: Methanobactinsmentioning
confidence: 94%
“…These results demonstrate that the main isomer of the switch can be tuned by choosing the appropriate irradiation wavelength. Further studies on a series of derivatives of oxazolone compounds revealed that a bathochromic shift in the absorption spectrum occurs when the methyl group at R 1 position is replaced with a phenyl group 48. Substitution with a para or ortho methoxy group at R 2 position results in absorption spectra in the visible range, which is desirable for use as a photoswitch in biological systems.…”
Section: Recent Applications Of the Photoisomerizable Azobenzene Smentioning
confidence: 99%
“…4-Arylidene-5(4 H )-oxazolones are closely related to imidazolones, which are precursors of the former ( Figure 1 b). Unsaturated oxazolones are also luminescent and they have additional remarkable photophysical properties that include two-photon absorption (TPA), up-conversion, nonlinear optical properties and unique behavior as molecular switches [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%